Fusarium Root Rot of Acacia nilotica and its Control - Singh, Bhawani, Jamaluddin (Indian Forester, 2000)
Fusarium pallidoroseum caused severe mortality of A. nilotica seedlings in nursery. It is one of the serious problems to developing healthy nursery stock. In order to manage this problem, VAM fungi, Rhizobium, Trichoderma viride and fungicides like Bavistin and Dithane M-45 were tried to control this disease. It has been found that biofertilizers like VAM fungi and Rhizobium along with antagonistic fungus T. viride were highly effective in controlling the root rot problem of A. nilotica. This is recommended as the effective control to develop the healthy nursery stock for plantation.